2020
DOI: 10.4236/as.2020.1112081
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Physical Properties of Cashew Nuts from Three Main Production Areas in Côte d’Ivoire

Abstract: The aim of our study was to evaluate physical properties of cashew nuts from the three main production areas in Côte d'Ivoire namely Bondoukou, Dabakala and Mankono after 6 months of storage in identical conditions. Sample cashew nuts have been collected from farmers randomly selected in 20 localities far enough apart and also veritable purveyors of nuts. The physical traits of the raw cashew nuts and their different parts were evaluated by standard methods. As results, our data showed that despite the similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In alignment with the findings of [6], our analysis of dimensional parameters further reinforces the significance of specific attributes in determining the industrial yield of cashew nuts within this germplasm. Stéphane et al's research indicates a positive correlation between the mass of cashew nuts and their length, width, and thickness.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In alignment with the findings of [6], our analysis of dimensional parameters further reinforces the significance of specific attributes in determining the industrial yield of cashew nuts within this germplasm. Stéphane et al's research indicates a positive correlation between the mass of cashew nuts and their length, width, and thickness.…”
Section: Resultssupporting
confidence: 82%
“…Cashew kernel processing involves a series of operations, including roasting, cracking, shell removal, peeling the kernel peel, and grading based on size, shape, and color [6]. The grading of cashew nuts is determined by international quality standards such as those of the Association of Food Industries (AFI) in the US and by the legislation of each exporting country [7].…”
Section: Introductionmentioning
confidence: 99%
“…A further evaluation was carried out by comparing some of the cashew nut properties with cashew nuts originating from several countries as published by several researchers. Table 2 represents the physical properties of cashew nuts from India (Balasubramanian 2001), Nigeria (Kilanko et al 2020), and Ivory Coast (Stéphane et al 2020). It was revealed that the cashew nut from Central Java was dominant with a small-medium size, where the mass of the nut was 5.42 ± 0.99 g (the moisture content was 7.63% wb).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from work done by the national agricultural research center (CNRA) on genotypic screening of high-yielding cashew nuts [18], and cashew nut pests [59], cashew nut industry has also benefited from few research and development projects in nut quality management. No scientific research has yet been done on the characterization of the physical and sanitary features of raw cashew nuts, which would enable the development of the map of nut quality according to the production regions in Côte d'Ivoire [16].…”
Section: Present Breeding Statusmentioning
confidence: 99%
“…The national cashew nut production of Côte d'Ivoire increased by 31% over three years, from 480,000 tons in 2013 to 703,000 tons in 2015 [2,15] (Table 3). Despite the enormous potential for cashew in Côte d'Ivoire, production is characterized not only by poor yields but also by a less competitive quality of nuts with respect to global standard [16,17]. Moisture routinely exceeds the required 10% level, generally regarded as poor or undesirable [18].…”
Section: Introductionmentioning
confidence: 99%